2005
DOI: 10.1359/jbmr.050610
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Detector Row CT Imaging of Vertebral Microstructure for Evaluation of Fracture Risk

Abstract: We applied MDCT for in vivo evaluation of the microarchitecture of human vertebrae. Microstructure parameters, such as structure model index, Euler's number, and bone volume fraction, revealed higher relative risk for prevalent vertebral fracture than did BMD obtained by DXA. Thus, microstructure analysis by MDCT, together with simultaneously obtained volumetric BMD values, is useful for clinical assessment of fracture risk.Introduction: BMD measurement by DXA alone has limitations in predicting fracture, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
181
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 204 publications
(193 citation statements)
references
References 32 publications
7
181
0
2
Order By: Relevance
“…the distal radius and tibia (14,15). The rapid diffusion of multi-detector CT systems also opens opportunities for TB structure analysis in the axial skeleton (16) although radiation exposure is a concern. However, remarkable progress in high-resolution MRI during the past 10 years now offers a new tool for TB structure assessment [reviews: (8,(17)(18)(19)(20)].…”
Section: Non-invasive Assessment Of Bone Architecture Mri Versus Ctmentioning
confidence: 99%
See 1 more Smart Citation
“…the distal radius and tibia (14,15). The rapid diffusion of multi-detector CT systems also opens opportunities for TB structure analysis in the axial skeleton (16) although radiation exposure is a concern. However, remarkable progress in high-resolution MRI during the past 10 years now offers a new tool for TB structure assessment [reviews: (8,(17)(18)(19)(20)].…”
Section: Non-invasive Assessment Of Bone Architecture Mri Versus Ctmentioning
confidence: 99%
“…A further potential motivation is the study of the structural manifestations of metabolic bone disease such as renal osteodystropy (166). Evidence for these developments is the rapid growth of the clinical literature (8,83,84,127,145,165,(167)(168)(169)(170)(171)(172) and also, to a lesser extent, the increased use of CT to characterize TB (14)(15)(16)(173)(174)(175)(176)(177).…”
Section: Clinical Applications Of Trabecular Bone Microstructural Anamentioning
confidence: 99%
“…The BV/TV, Tb.N, Tb.Th, and Tb.Sp, connectivity and structure model index (SMI) are calculated two-dimensionally using plate model assumptions [131,132] or direct three-dimensional measures [133]. Due to the lower spatial resolution comparing with the pQCT or μQCT, the partial volume effect is relatively large.…”
Section: Assessment Of the Trabecular Microarchitecture With Mdctmentioning
confidence: 99%
“…Studies have shown a moderate correlation between the MDCT and μQCT in trabecular microstructure assessment (r=.44-0.99) [132,134]. The advantage of the MDCT technique is that both the central or peripheral regions of the skeleton can be assessed, such as the spine, proximal femur and extremity [132,133,135]. Studies indicated that the BV/TV and SMI measured from lumbar spine by MDCT provided a superior result in predicting fracture risk and therapeutic evaluation than BMD measurement with DXA or QCT [133,136].…”
Section: Assessment Of the Trabecular Microarchitecture With Mdctmentioning
confidence: 99%
See 1 more Smart Citation